2020
DOI: 10.1177/0300060520976027
|View full text |Cite
|
Sign up to set email alerts
|

Combining real-time elastography with fine-needle aspiration biopsy to identify malignant thyroid nodules

Abstract: Objectives To evaluate the diagnostic performance of real-time elastography (RTE) combined with fine-needle aspiration (FNA) biopsy in identifying malignant thyroid nodules. Methods This was a single-centre, retrospective study and involved patients who had underogone partial or total thyroidectomy from 01 January 2014 to 31 December 2018 at our centre. Eligible patients were at least18 years of age, had reliable grayscale ultrasound imaging results, a RTE evaluation and had undergone a FNA biopsy. Results Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Sengul et al ( 31 ) found that SE score could affect the clinical decision-making for patients with indeterminate FNA cytology. Zhu et al ( 32 ) reported that a high SE score was a significant predictor for malignancy. However, SE was challenged and criticized due to its operator dependency ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sengul et al ( 31 ) found that SE score could affect the clinical decision-making for patients with indeterminate FNA cytology. Zhu et al ( 32 ) reported that a high SE score was a significant predictor for malignancy. However, SE was challenged and criticized due to its operator dependency ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, elastography has become available for thyroid nodule evaluation as reported in many studies, which is emerging as a potential method for the differentiation of benign and malignant thyroid nodules and may provide additional information to support clinical decision-making (29). Some studies (30)(31)(32)(33) reported that strain elastography (SE) was useful for the prediction of malignancy and differentiation of thyroid nodules with indeterminate FNA cytology. Sengul et al (31) found that SE score could affect the clinical decision-making for patients with indeterminate FNA cytology.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of diagnostic techniques for thyroid malignancies ( 20 , 21 ), there is a rising trend in the number of patients requiring thyroid surgery. IONM technology has been widely utilized in thyroid surgery to real-time monitor the function of the recurrent laryngeal nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The above‐mentioned studies investigated elastography before FNA. Additionally elastography can also be used in combination with FNA to improve the final diagnostic accuracy, as studied by Zhu et al 94 This might be problematic for the indeterminate nodules, however Qiu et al found in their systematic review that shear‐wave elastography and strain ratio elastography are more efficient for differentiation of indeterminate thyroid nodules 95 . In addition, they concluded that the combination of elastography and other ultrasound techniques improves evaluation of indeterminate thyroid nodules 95 .…”
Section: Diagnosismentioning
confidence: 99%